APLIKASI PEMILIHAN PERAMALAN METODE SINGLE MOVING AVERAGE ATAU METODE WEIGHTED MOVING AVERAGE BERDASARKAN ERROR - Imam Solikin; Septa Hardini; Dirut Saputra; Rina Emelia Rajagukguk (P3M Institut Teknologi Pagar Alam, 2023)
This research was conducted at Jimmy Fish, which is a business engaged in the sale and purchase of fish seeds including carp seeds, tilapia seeds, catfish seeds, catfish seeds. This research is a development of previous research where previous research applications that were built only used the weighted moving average (WMA) method and there was no error calculation. The development carried out in this study, the application was built using two forecasting methods, namely the single moving average (SMA) and weighted moving average (WMA) methods equipped with error calculations. Error calculation is used to choose which method is more suitable for use in making decisions to buy stock of fish seeds. The application development method used is the waterfall model. The purpose of this research is to determine the appropriate method for purchasing fish stock for the next period, simplifying and speeding up performance.